Evaluación de la obtención de un conservante de alimentos natural basado en la extracción de alicina para aplicarlo en frutas y/o verduras (2020)
The experimentation of this project was carried out in home conditions considering that the project was developed in the midst of the national situation brought about by the Covid-19 pandemic. This project is based on the extraction of a biocomposite from one of the most used vegetables in the world: The Allium Sativum species or garlic. Garlic is made up of different organosulfur elements that give it each of its characteristics. Among these biocomposites is allicin (diallyl thiosulfinate) that starts from the interaction between the enzyme allinase in garlic and a non-protein amino acid called Alina when the garlic clove is exposed to stress situations. Taking into account the properties of this biocomposite, an allicin extract was obtained for its antifungal evaluation on environmental fungi and its effect on a sample of strawberries. For its extraction, an ethanol-water solution was used as a solvent and maceration at room temperature was used as an extraction method. An experimental development was carried out to determine the best garlic-solvent ratio using 25, 50 and 100g of garlic for 100mL, being the ratio 25g of garlic100mL of solvent the one used for the treatment in strawberries.